Delayed breast cancer relapse with pleural metastasis and malignant pleural effusion after long periods of disease‐free survival. Issue 9 (26th October 2018) - Rawindraraj, Antony Divananth; Zhou, Christine Yang; Pathak, Vikas
Abstract : Breast cancer relapse remains a common cause of morbidity and mortality in patients who undergo initial treatment with surgery and with or without concurrent chemotherapy or radiation. Relapse rates remain high within the first decade after initial treatment, after which the risk of relapse decreases. While common within the first year of breast cancer diagnosis, pleural metastasis with malignant pleural effusion (MPE) after 10–12 years of a disease‐free period is rare. Here, we present two uncommon cases of delayed breast cancer relapses with pleural metastasis, which caused MPEs. Abstract : Breast cancer relapse rates remain high within the first decade after initial treatment, after which the risk of relapse decreases. While common within the first year of breast cancer diagnosis, pleural metastasis with malignant pleural effusion (MPE) after 10–12 years of a disease‐free period is rare. This case series presents two uncommon cases of delayed breast cancer relapses with pleural metastasis, which caused MPEs.